2005
DOI: 10.1097/01.bsd.0000128692.44276.cf
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Epidural Hematoma After Removal of an Epidural Catheter

Abstract: We report a case of spinal epidural hematoma after removal of an epidural catheter. The patient had no background of anticoagulant therapy or coagulopathy; sudden severe back pain occurred immediately after removal of the catheter. The chance of this occurring is estimated to be between 1:150,000 and 1:190,000. We studied 40 previous reports from 1952 to 2000, and we also investigated anticoagulant therapy and pathologic states, puncture difficulties and bleeding at the point of insertion, and its onset. In 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
(9 reference statements)
0
26
0
Order By: Relevance
“…So suffi cient education/ knowledge of epidural catheter removal is important. Miyazaki et al [15] reported that the initial symptoms of SEH were recognized within 24 h after the removal of an epidural catheter in 50% of 40 patients with SEH. If a patient presents with symptoms suggesting spinal cord compression after epidural catheter removal, SEH formation should be suspected.…”
Section: Discussionmentioning
confidence: 98%
“…So suffi cient education/ knowledge of epidural catheter removal is important. Miyazaki et al [15] reported that the initial symptoms of SEH were recognized within 24 h after the removal of an epidural catheter in 50% of 40 patients with SEH. If a patient presents with symptoms suggesting spinal cord compression after epidural catheter removal, SEH formation should be suspected.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, epidural anesthesia has potential complications such as epidural hematoma, spinal cord injury, and high levels of anesthesia [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for SEH associated with epidural anesthesia are female sex, old age, a history of gastrointestinal bleeding, anticoagulant therapy, coagulopathy, hepatic dysfunction, and difficult or traumatic epidural catheterization and bleeding at the puncture site [2, 5, 13]. Even if bleeding occurs in the epidural space, it usually stops rapidly [13]; however, a large hematoma may accumulate in the epidural space of patients with coagulopathy or liver dysfunction and those taking anticoagulants [13]. Spinal epidural hematoma may occur in patients with normal clotting function [5, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Even if bleeding occurs in the epidural space, it usually stops rapidly [13]; however, a large hematoma may accumulate in the epidural space of patients with coagulopathy or liver dysfunction and those taking anticoagulants [13]. Spinal epidural hematoma may occur in patients with normal clotting function [5, 13, 14]. It may present when an epidural catheter is in situ or after its removal [210].…”
Section: Discussionmentioning
confidence: 99%